Trade Related Intellectual Property Rights (Trips) - Ratnalikar, D. V. (Journal of Engineering Education Transformations, 2005)
India joined as the original signatories of the first General Agreement of Tariff and Trade (GAD) way back in 1947, along with other 26 countries. As a consequence of the Bretton Woods Conference, three international institutions, namely, International Bank of Reconstruction and Development (World Bank). International Monetory Fund (IMF) and International Trade Organisation (ITO) were established.